Diffusion in Ni–Zr Melts: Insights from Statistical Mechanics and Atomistic Modeling. Issue 12 (11th September 2018) - Kromik, Andreas; Levchenko, Elena V.; Massobrio, Carlo; Evteev, Alexander V.
Abstract: An accurate database of diffusion properties of Ni–Zr melts is generated within the framework of the molecular‐dynamics method in conjunction with a semi‐empirical many‐body interatomic potential. The reliability of the model description of Ni–Zr melts is confirmed via comparison of the simulation results with the existing experimental data on diffusion properties of Ni–Zr melts. A statistical mechanical formalism is employed to understand the behavior of the cross‐correlation between the interdiffusion flux and the force caused by the difference in the average random accelerations of atoms of different species in the short time limit t → 0 . This theoretical description is exploited to analyze the simulation data on the diffusion properties of Ni–Zr melts. On this basis, it is found that in the composition range 0.25 < ∼ x c Ni < ∼ x 0.5 both single‐particle and collective diffusion dynamics slow down homogeneously upon undercooling of Ni–Zr melts. Furthermore, it is inferred that such homogeneous dynamical slowdown is related to the enhanced stability of undercooled melt against crystallization. As a consequence, Ni–Zr alloys within this composition range are identified as viable glass formers. Abstract : The binary Ni–Zr system has attracted a great interest as a base system for developing an important class of multicomponent Zr‐based bulk metallic glasses (BMGs) produced by melt processing. This contribution presents theoretical and computational insights into diffusion properties of Ni–Zr melts which are in close agreement with experiments.